Synthesis and characterization of polymeric biodegradable hydrogels for drug delivery - Teo, Wang Wang. (2010)
Smart hydrogels, such as stimuli-responsive reversible hydrogels, have great potential in biomedical and pharmaceutical applications, especially in site-specific controlled drug-delivery systems, cell encapsulation, and tissue repair. Among the stimuli in the biomedical application, temperature and pH are the most popular physical and chemical stimuli, respectively. In this project, we developed one kind of pH/thermal dual-responsive reversible hydrogels. The hydrogels are in-situ physical hydrogels driven by hydrophobic interactions. We have attempted to prepare two types of precursors: 1) linear biodegradable disulfide-containing polymers comprising both hydrophilic poly(ethylene glycol) (PEG) segment and thermogelling hydrophobic poly(propylene glycol)(PPG) oligomers, and 2) comb-like biodegradable disulfide-containing polymers with grafting both hydrophilic PEG segment and thermogelling hydrophobic PPG oligomers. The aqueous polymer solutions by changes in external temperature and pH can result in in-situ reversible hydrogels formation. Therefore, the smart hydrogels allows in-situ encapsulations of active bioagents like drugs in the aqueous medium avoiding denaturing conditions, so it is well suited for drug formulation and administration. In addition, biocompatibility and biodegradability of the formed hydrogels will further benefit for potential in vivo and clinical applications.